Binge Drinking, Alone or With Cannabis, During Adolescence Triggers Different Effects on Immediate Visual Memory in Men and Women - Vinader-Caerols, Concepción; Monleón, Santiago (Frontiers in Psychiatry, 2021)
Background: This study examines the interaction between a history of binge drinking (BD), alone or with cannabis consumption, and the effects of acute alcohol exposure on immediate visual memory (IVM) (faces memory task, scenes memory task and IVM-IQ) in adolescents of both sexes. Method: 290 adolescents, grouped into refrainers, binge drinkers and subjects with a history of simultaneous BD/Cannabis co-use, received a risk dose of alcohol or a control drink. Results: Consumption Pattern (refrainers versus binge drinkers versus BD/Cannabis consumers) was not significant, while Treatment (acute alcohol versus control drink) was significant in both sexes. Also, male binge drinkers’ performance in the faces memory task was poorer than that of refrainers and BD/Cannabis consumers who consumed the control drink. BD/Cannabis consumers performed this task as capably as refrainers. In women, binge drinkers performed better than refrainers in scene memory and IVM-IQ tests when given alcohol, and binge drinkers performed worse than refrainers after consuming the control drink. Conclusions: Acute alcohol consumption worsens IVM. Cannabis exerts a buffering effect in men. A cognitive tolerance effect is observed in women. Exposure during adolescence to alcohol, alone or with cannabis, can trigger different cognitive effects in men and women that could endure into adulthood.